Sulfonation of cPTFE Film grafted Styrene for Proton Exchange Membrane Fuel Cell - Yohan, Yohan (UI Scholars Hub, 2007)
Sulfonation of cPTFE Film grafted Styrene for Proton Exchange Membrane Fuel Cell. Sulfonation of γ-ray iradiated and styrene-grafted crosslinked polytetrafluoroethylene film (cPTFE-g-S film) have been done. The aim of the research is to make hydropyl membrane as proton exchange membrane fuel cell. Sulfonation was prepared with chlorosulfonic acid in chloroethane under various conditions. The impact of the percent of grafting, the concentration of chlorosulfonic acid, the reaction time,and the reaction temperature on the properties of sulfonated film is examinated. The results show that sulfonation of surface-grafted films is incomplete at room temperature. The increasing of concentration of chlorosulfonic acid and reaction temperature accelerates the reaction but they also add favor side reactions. These will lead to decreasing of the ion-exchange capacity, water uptake, and proton conductivity but increasing the resistance to oxidation in a perhidrol solution. The cPTFE-g-SS membrane which is resulted has stability in a H2O2 30% solution for 20 hours.